Study protocol for an observational study of cerebrospinal fluid pressure in patients with degenerative cervical myelopathy undergoing surgical deCOMPression of the spinal CORD: the COMP-CORD study - Armin Curt; Carl Moritz Zipser; Nikolai Pfender; Jose Miguel Spirig; Michael Betz; Jose Aguirre; Markus Hupp; Mazda Farshad; Martin Schubert (BMJ Open)
Introduction Degenerative cervical myelopathy (DCM) is a disabling spinal disorder characterised by sensorimotor deficits of upper and lower limbs, neurogenic bladder dysfunction and neuropathic pain. When suspected, cervical MRI helps to reveal spinal cord compression and rules out alternative diagnoses. However, the correlation between radiological findings and symptoms is weak. Cerebrospinal fluid pressure (CSFP) analysis may complement the appreciation of cord compression and be used for intraoperative and postoperative monitorings in patients undergoing surgical decompression.Methods and analysis Twenty patients diagnosed with DCM undergoing surgical decompression will receive standardised lumbar CSFP monitoring immediately before, during and 24 hours after operation. Rest (ie, opening pressure, CSF pulsation) and stimulated (ie, Valsalva, Queckenstedt’s) CSFP—findings in DCM will be compared with 20 controls and results from CSFP monitoring will be related to clinical and neurophysiological findings. Arterial blood pressure will be recorded perioperatively and postoperatively to calculate spinal cord perfusion pressure and spinal vascular reactivity index. Furthermore, measures of CSFP will be compared with markers of spinal cord compression by means of MR imaging.Ethics and dissemination The study protocol conformed to the latest revision of the Declaration of Helsinki and was approved by the local Ethics Committee of the University Hospital of Zurich (KEK-ZH number PB-2016-00623). The main publications from this study will cover the CSFP fluid dynamics and pressure analysis preoperative, perioperative and postoperative correlated with imaging, clinical scores and neurophysiology. Other publications will deal with preoperative and postoperative spinal perfusion. Furthermore, we will disseminate an analysis on waveform morphology and the correlation with blood pressure and ECG. Parts of the data will be used for computational modelling of cervical stenosis.Trial registration number ClinicalTrials.gov Registry (NCT02170155).